Perbandingan Sistem, Strategi dan Berbeda Manufaktur yang Dikembangkan PTKI dengan Multikultural - Seten Hartedi; Alfauzan Amin (UIN Fatmawati Sukarno Bengkulu, 2024)
The context of pluralism, multiculturalism, multiethnicity and religion in Indonesian society is very important. Therefore, serious attention is needed from various parties, so that unity and togetherness are not divided. Although the above problems have subsided, it does not mean that the problems have resolved themselves, because in many cases the implementation of Article 13A of the Education Law at the administrative level does not run as it should. Basically, this provision has three specific objectives: 1) Avoiding deviations from religious norms or misinterpretations that may arise if teachers are taught by teachers who do not share the same faith; 2) If teachers have the same beliefs as students, then religious harmony can be better maintained between other students; and 3) Professionalism in organizing religious training and education. The application of religion in multicultural education in the world of education can be a solution to disputes in society. In comparative research, several approaches can be used to compare groups, such as experiments, case studies, or secondary data analysis. This research focuses on analyzing the differences or relationships between the variables studied in two or more different groups or situations. The objective can be modified to understand the influence of a variable on different groups, to identify factors that influence differences and similarities between groups in order to compare the effectiveness of two or more strategies and differences in manufacturing in developing PTKI with multiculturalism.